Lactational performance of Jersey cows given Napier fodder (Pennisetum purpureum) with and without protein concentrates in the semi-humid tropics - Muinga, R.W.; Thorpe, W.R.; Topps, J.H. (Springer, 1993)
Two experiments with 12 and 18 lactating Jersey cows respectively were carried out in the coastal semi-humid zone of Kenya to assess the performance arising from the feeding of chopped Napier fodder (Pennisetum purpureum) given ad libitum with and without one of three sources of protein; fishmeal, copra cake and freshly cut Leucaena (Leucaena leucocephala). Each source supplied approximately 300 g crude protein daily. Dry matter intakes of Napier fodder fed alone averaged 7.1 and 5.5 kg in Experiments 1 and 2 respectively. Additional protein did not affect Napier fodder intake, but total intakes of dry matter were higher for the cows receiving the protein supplements, differences which were significant in experiment 2. Average daily milk production from cows fed Napier fodder alone was 6.4 and 4.2 kg in Experiments 1 and 2 respectively. The additional 300g crude protein increased milk production by 1.0 to 1.6 kg/day, increases which, except that for fishmeal, were significant. Weight losses of the cows were either reduced or changed to weight gains by the provision of protein. The results are assessed in relation to the energy and protein requirements for milk production.